Do agricultural contracts affect grain prices? Evidence from Mexico - Santiago Guerrero (Banco de México, 2012)
In the late 80's and early 90's Mexico eliminated minimum price policies of main agricultural commodities and substituted those policies by government operated contract markets. Contracts can help smooth price variations and facilitate risk-sharing but their impact on price levels is uncertain. We simultaneously estimate the impacts of quantity supplied sold via contracts and the cash market on cash prices for grains participating in contracts: wheat, corn, soybeans and sorghum. By doing so we estimate an inverse grain demand function using supply shifters and other exogenous variables as exclusion restrictions. Our findings show that quantity supplied sold via contracts is a more important determinant of prices than quantity supplied in the cash market. A 10% increase of volume sold via contracts is estimated to reduce cash market prices by 2.5 %. Additionally, we find no evidence that more contracts affect prices by reducing quantity supplied in the cash market.
Keywords: Q11; Q14; Q18; 330; Contracts; Inverse Demand; Three Stage Least Squares; Grains; Supply Shifters